Discovery of Compounds that Positively Modulate the High Affinity Choline Transporter - Choudhary, Parul; Armstrong, Emma J.; Jorgensen, Csilla C.; Piotrowski, Mary; Barthmes, Maria; Torella, Rubben; Johnston, Sarah E.; Maruyama, Yuya; Janiszewski, John S.; Storer, R. Ian; Skerratt, Sarah E.; Benn, Caroline L. (Frontiers in Molecular Neuroscience, 2017)
Cholinergic hypofunction is associated with decreased attention and cognitive deficits in the central nervous system in addition to compromised motor function. Consequently, stimulation of cholinergic neurotransmission is a rational therapeutic approach for a variety of neurological conditions. High affinity choline uptake (HACU) into acetylcholine (ACh)-synthesizing neurons is critically mediated by the sodium- and pH-dependent high-affinity choline transporter (CHT, encoded by the SLC5A7 gene). This transporter is comparatively well-characterised but otherwise unexplored as a potential drug target. We therefore sought to identify small molecules that would enable testing of the hypothesis that positive modulation of CHT mediated transport would enhance activity-dependent cholinergic signalling. We utilized existing and novel screening techniques for their ability to reveal both positive and negative modulation of CHT using literature tools. A screening campaign was initiated with a bespoke compound library comprising both the Pfizer Chemogenomic Library (CGL) of 2753 molecules designed specifically to help enable the elucidation of new mechanisms in phenotypic screens; and 887 compounds from a virtual screening campaign to select molecules with field-based similarities to reported negative and positive allosteric modulators. We identified a number of active and previously unknown structurally distinct molecules that could be used as tools to further explore CHT biology or as a starting point for further medicinal chemistry.